Slope Stabilization by Using Bamboo - Ahmad Nizam, Muhammad Firdaus; Badrul Din, Muhammad Hazim; Mohd Anuar, Akmal Arif; Mat Nor, Ahmad Hakimi (Multidisciplinary Applied Research and Innovation, 2022)
Slope failure have occur in Malaysia several times and it could be a threat towards people which the slope failure leads to landslide. Analysing and prioritize of the slope we develop a way for slope stabilization. The plan was to made a slope stabilization out of bamboo and discuss on how the plan for the slope model in AutoCAD. The slope stabilization model also need to determine type of joints to be used and ways to install the bamboo block model at the site. The bamboo block stabilization slope model should be able to resist the slope failure and work as a retaining wall. By doing research from several types of sources such as online journal, the idea on how the model of the bamboo was taken from concept of gabion block and crib wall. To achieve the best result of the model, two types of model were presented by using an application that could draw the plan and the detail drawing of the blocks model. The application that have been used in these research are AutoCAD and SketchUp to build the 3D modelling and plan. This study aim to build the best model of bamboo block to use as a slope stabilization, because have a high compressive strength than steel and had the price is economical. As the result, the design model achieve and suitable for slope stabilization. The design include the types of the joint that had been choose for slope stabilization and ways on how to install it at the sites.